Hardness, tensile and microstructure assessment of carbon/glass hybrid composite laminate / Ahmad Fuad Ab Ghani and Jamaluddin Mahmud - Ab Ghani, Ahmad Fuad; Mahmud, Jamaluddin (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Hybrid composites are often made by combining the high and low modulus fibers. The high modulus fiber, such as Carbon fiber provides the stiffness and load bearing qualities, whereas the low modulus fiber, such as glass fiber makes the composite more durable and low in cost. Nevertheless, the optimum arrangement between these fibers is still under comprehensive investigation. This paper assesses the hardness, tensile and microstructure of Hybrid Composite Laminates by varying the arrangement of Carbon Fiber Reinforced Polymer (CFRP) and Glass Fiber Reinforced Polymer (GFRP). Hardness and Tensile Tests were carried out on seven different layup arrangements of the Carbon-Glass Hybrid Composite Laminates. Hardness tests were performed using micro hardness tester and pyramid shape indenter. Tensile Tests were performed in accordance to ASTM D3039 to determine the Modulus of Elasticity, E and Tensile Strength, UTS. In addition, the failure modes of the laminates were also observed. Microstructural analyses were carried out using Scanning Electron Microscope (SEM). In general, the results show that the hybridization effect has improved proportionately the Modulus of Elasticity of the hybrid composite laminates compared to GFRP constituents. However, it is also interesting to observe that the hybridization effect does not necessarily improves the hybrid laminate Tensile Strength, UTS due to delamination and incompatibility at the interface between CFRP the GFRP bond.